Mind the Gaps: Managing Mutual Dependence in Relations among Levels of Government - Charbit, Claire (OECD Working Papers on Public Governance, 2009)
OECD member and non-member governments are actively looking for ways to facilitate and improve the relationships among levels of government. These relationships lie between the central and sub-national levels, as well as among peer levels (i.e., among ministries, across regions, between municipalities). They can also be seen in individual public management disciplines, such as fiscal relations, human resource management (HRM), regulatory management and e-government. This report arises from a request by the OECD's Public Governance Committee to look more closely at ways to build more effective relations among levels of government